Racial Differences in Disease Presentation and Management of Intracranial Meningioma - Anzalone, C. Lane; Glasgow, Amy E.; Van Gompel, Jamie J.; Carlson, Matthew L. (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objective/Hypothesis The aim of the study was to determine the impact of race on disease presentation and treatment of intracranial meningioma in the United States.Study Design This study comprised of the analysis of a national population-based tumor registry.Methods Analysis of the surveillance, epidemiology, and end results (SEER) database was performed, including all patients identified with a diagnosis of intracranial meningioma. Associations between race, disease presentation, treatment strategy, and overall survival were analyzed in a univariate and multivariable model.Results A total of 65,973 patients with intracranial meningiomas were identified. Of these, 45,251 (68.6%) claimed white, 7,796 (12%) black, 7,154 (11%) Hispanic, 4,902 (7%) Asian, and 870 (1%) patients reported “other-unspecified” or “other-unknown.” The median annual incidence of disease was lowest among black (3.43 per 100,000 persons) and highest among white (9.52 per 100,000 persons) populations (p < 0.001). Overall, Hispanic patients were diagnosed at the youngest age and white patients were diagnosed at the oldest age (mean of 59 vs. 66 years, respectively; p < 0.001). Compared with white populations, black, Hispanic, and Asian populations were more likely to present with larger tumors (p < 0.001). After controlling for tumor size, age, and treatment center in a multivariable model, Hispanic patients were more likely to undergo surgery than white, black, and Asian populations. Black populations had the poorest disease specific and overall survival rates at 5 years following surgery compared with other groups.Conclusion Racial differences among patients with intracranial meningioma exist within the United States. Understanding these differences are of vital importance toward identifying potential differences in the biological basis of disease or alternatively inequalities in healthcare delivery or access Further studies are required to determine which factors drive differences in tumor size, age, annual disease incidence, and overall survival between races.
Keywords: meningioma; radiosurgery; microsurgery; race; ethnicity; epidemiology